2008
DOI: 10.3748/wjg.14.4984
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signaling and T-type calcium channels in cancer cell cycling

Abstract: Regulation of intracellular calcium is an important signaling mechanism for cell proliferation in both normal and cancerous cells. In normal epithelial cells, free calcium concentration is essential for cells to enter and accomplish the S phase and the M phase of the cell cycle. In contrast, cancerous cells can pass these phases of the cell cycle with much lower cytoplasmic free calcium concentrations, indicating an alternative mechanism has developed for fulfilling the intracellular calcium requirement for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 52 publications
4
108
1
2
Order By: Relevance
“…Many studies have been conducted to evaluate how the regulatory system of intracellular calcium homeostasis and the associated calcium signaling pathways are altered in breast cancer cells compared with normal mammary gland cells. A recent review summarizes the possible roles of T-type calcium channels in breast cancer progression (30). The essential roles of the SOCC Orai1 and the signaling molecule Stim1 in breast cancer metastasis formation was recently reported (31).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted to evaluate how the regulatory system of intracellular calcium homeostasis and the associated calcium signaling pathways are altered in breast cancer cells compared with normal mammary gland cells. A recent review summarizes the possible roles of T-type calcium channels in breast cancer progression (30). The essential roles of the SOCC Orai1 and the signaling molecule Stim1 in breast cancer metastasis formation was recently reported (31).…”
Section: Discussionmentioning
confidence: 99%
“…27 The mechanisms of the deregulation of calcium signaling have been shown through T-type calcium channels, calcium pumps/exchangers, vitamin D, and calcium-sensing receptors. [27][28][29][30][31][32][33] Calcium and vitamin D pathways have been found to be especially important in activating the genetic pathways required for keratinocyte differentiation. 34,35 Bikle et al 35 showed that squamous cell carcinoma cell lines failed to respond to the prodifferentiating actions of vitamin D. Alterations of calcium signaling have also been linked to carcinomas of breast, colon, esophagus, liver, ovarian, and prostate origin.…”
Section: Wnt/b-catenin Signalingmentioning
confidence: 99%
“…In addition, an antagonist selective for T-type Ca 2þ channels, mibefradil, has been proposed recently as a sensitizing agent with activity in vivo in combination with chemo-(9) or radiotherapy (10). Aberrant expression of T-type Ca 2þ channels in cancer cells is thought to promote cell survival, proliferation, and motility (3,11); however, the molecular mechanisms for these effects are poorly understood.…”
Section: Introductionmentioning
confidence: 99%